2021
DOI: 10.3390/en14123451
|View full text |Cite
|
Sign up to set email alerts
|

PAH and POP Presence in Plastic Waste and Recyclates: State of the Art

Abstract: The presence of different pollutants in recycled plastics is reviewed in this article. The desirable circular economy of plastics should be linked to the availability of clean recycled plastics with a non-significant and small to nil amount of substances of concern. Different researchers found polycyclic aromatic hydrocarbons (PAHs) and Persistent Organic Pollutants (POPs), such as brominated flame retardants (BFRs), pesticides, dioxins and furans (PCDD/Fs and PBDD/Fs) in plastic recyclates. This represents an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Most recycled materials have an inherent degree of anthropogenicity which may arise either during production of the original material or during the recycling process or both. This introduces the potential for inadvertent inclusion of contaminants (Schlummer et al, 2004) as has been observed in the past (Rigby et al, 2015(Rigby et al, , 2021Fernandes et al, 2019;Gerber et al, 2020;Mohajerani and Karabatak, 2020;Conesa et al, 2021). The type of contamination depends on the origins of the material or the recycling process, e.g., chicken pecking blocks made from recycled ash can contain PCDD/Fs, recycled paper and card materials can contain flame retardants and perfluorinated alkyl substances (PFAS) that were originally part of the printing and labelling material or a grease-repellent coating.…”
Section: Introductionmentioning
confidence: 96%
“…Most recycled materials have an inherent degree of anthropogenicity which may arise either during production of the original material or during the recycling process or both. This introduces the potential for inadvertent inclusion of contaminants (Schlummer et al, 2004) as has been observed in the past (Rigby et al, 2015(Rigby et al, , 2021Fernandes et al, 2019;Gerber et al, 2020;Mohajerani and Karabatak, 2020;Conesa et al, 2021). The type of contamination depends on the origins of the material or the recycling process, e.g., chicken pecking blocks made from recycled ash can contain PCDD/Fs, recycled paper and card materials can contain flame retardants and perfluorinated alkyl substances (PFAS) that were originally part of the printing and labelling material or a grease-repellent coating.…”
Section: Introductionmentioning
confidence: 96%
“…Among the compounds studied, PAHs, dioxins, and furans (PCDD/Fs) stand out. These compounds have also been detected in products made from plastics [19] and in recycled plastics by different procedures [20]. The rationale for the need for this review is therefore the importance of the presence of carcinogenic and mutagenic compounds in the different microplastics present in aquatic and terrestrial environments, which will be incorporated into the food chain, eventually reaching human beings.…”
Section: Introductionmentioning
confidence: 99%
“…Sánchez et al [5] presented an analytical method to determine combustion PAHs both in the gas phase and in the particles. These pollutants are present also in recycled plastic items, and have been identified as causing possible negative effects on this type of materials [6].…”
Section: Introductionmentioning
confidence: 99%